Peningkatan harga diri melalui layanan bimbingan dan konseling individu - Umar Latif; Zamratul Aini (Jurnal Konseling dan Pendidikan, 2020)
Fostered women are more vulnerable to psychological problems than fostered men. One psychological problem that is usually experienced by inmates is low self-esteem. one solution to improve self-esteem can be done through Islamic counseling services.The purpose of devotion-based research is to determine the effectiveness of Islamic counseling in increasing the self-esteem of the target people. The approach used in this research is Participatory Action Research. respondents involved in this study were all members of the Sigli Penitentiary Class III Prison Society. the results of the study found an increase in self-esteem in fostered citizens marked by the emergence of 5 of 7 aspects based on behavioral checklist indicators that are realistic, aware of strengths and weaknesses, aware of the position as a creature of God, assertive and independent.